Managing Urban Cultural Complexity: Perspectives on the Place of the Arts in Conflict Management - Skyllstad, Kjell (Lidé města, 2012)
Around the middle of the 1970s some musicians and music educators living in the Norwegian capital of Oslo met to discuss ways to create better harmony between the nature and extent of music activities in the capital and the increasing cultural complexity of its population caused by a sharp increase in immigration. This gave rise to the founding of the Intermusic center, a pioneer organization working towards bringing the population at large into living contact with the rich cultural heritage of the variegated immigrant population. The competence earned through this pioneering work was later to form the professional basis for launching the first official research undertaking evaluating the potential of a large scale school music program based on these resources. It was launched for the purpose of promoting better social relations among students in city public schools with differing populations of immigrant students. The paper attempts to discuss the methodical issues connected with an evaluative research program of this nature as well as those connected with practical teaching. An historical overview of institutionalized multicultural music teaching in Norway precedes a description of the Resonant Community project itself and is followed by an evaluative description of results and aftereffects. A concluding section discusses the future of multicultural education in Europe on the backdrop of the economic downturn and extremist actions.